Economic and Analytical Study for the Food gap of Wheat in Libya, and the possibility to reduce it during the period of 1995-2010. - Suleiman, Abdul Hamid Tahir; Allafi, Khaled A. Mousa (Al-Mukhtar Journal of Sciences, 2015)
Due to the continuing decrease of production and productivity of wheat, this in turn led to increase the food gap year by year, causing unbalance between supply and demand of wheat, so the problem statement of the study problem represented in inability of wheat production to meet the local requirement, this can be clear through the low of self-sufficiency rate of wheat. The food gap of wheat was estimated by 985.7 thousand tones 1995-2010, therefore, the government restored to fill the food gap through imports from beyond its borders, which impact on the balance of payments in general and the agricultural trade balance in particular. It can be seen that wheat production decreased by 2.40 thousand tones while the wheat consumption increased to 37.31 thousand tones. In addition, the per capita of production of wheat decreased by 0.757 Kg/y, while the per capita of consumption increased by 4.36 Kg/y. The food gap size of wheat amounted about 923.23 m/tones as average of 1995-2010, while the surplus size of local wheat consumption during the period of study amounted about 224.41 m/tones, this surplus led to develop the stock of wheat. On the other hand, through the estimation of food security coefficient during the period of study, ''as proportion'' of stock size to the average of annual local consumption, it can be seen that it ranged between 0.03 as a minimum and 0.58 as a maximum, where the annual average amounted about 0.35, this in turn led to the necessity of giving more attention to this crop and find out the appropriate policy to reduce the food gap.